Keratinocyte‐specific ablation of protease‐activated receptor 2 prevents gingival inflammation and bone loss in a mouse model of periodontal disease. (31st July 2018) - Francis, Nidhish; Ayodele, Babatunde A.; O'Brien‐Simpson, Neil M.; Birchmeier, Walter; Pike, Robert N.; Pagel, Charles N.; Mackie, Eleanor J.
Abstract: Chronic periodontitis is characterised by gingival inflammation and alveolar bone loss. A major aetiological agent is Porphyromonas gingivalis, which secretes proteases that activate protease‐activated receptor 2 (PAR2 ). PAR2 expressed on oral keratinocytes is activated by proteases released by P. gingivalis, inducing secretion of interleukin 6 (IL‐6), and global knockout of PAR2 prevents bone loss and inflammation in a periodontal disease model in mice. To test the hypothesis that PAR2 expressed on gingival keratinocytes is required for periodontal disease pathology, keratinocyte‐specific PAR2 ‐null mice were generated using K14‐Cre targeted deletion of the PAR2 gene ( F2rl1 ). These mice were subjected to a model of periodontitis involving placement of a ligature around a tooth, combined with P. gingivalis infection ("Lig + Inf"). The intervention caused a significant 44% decrease in alveolar bone volume (assessed by microcomputed tomography) in wildtype ( K14‐Cre:F2rl1 wt/wt ), but not littermate keratinocyte‐specific PAR2 ‐null ( K14‐Cre:F2rl1 fl/fl ) mice. Keratinocyte‐specific ablation of PAR2 prevented the significant Lig + Inf‐induced increase (2.8‐fold) in the number of osteoclasts in alveolar bone and the significant up‐regulation (2.4–4‐fold) of the inflammatory markers IL‐6, IL‐1β, interferon‐γ, myeloperoxidase, and CD11b in gingival tissue. These data suggest that PAR2 expressed on oral epithelial cells is a critical regulator of periodontitis‐induced bone loss and will help in designing novel therapies with which to treat the disease.